EVALUASI PROGRAM SI MAS BAIK (SISTEM MANAJEMEN SURAT BERBASIS ELEKTRONIK) DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK DI BIRO UMUM - Kurniawan, Bagus Ananda; Prasetijowati, Tri; Novitasari, Ellen (Universitas Lambung Mangkurat, 2023)
The purpose of this study was to evaluate the SI MAS BAIK (Electronic-Based Mail Management System) Program in improving the quality of public services at the General Bureau of the Regional Secretariat of East Java Province and to examine the efforts that need to be made to improve the Policy Evaluation of the SI MAS BAIK (Electronic-Based Mail Management System) Program. ) at the General Bureau of the Regional Secretariat of East Java Province. The sampling technique used is purposive sampling with a qualitative research approach. The results showed that: 1) The application of SI MAS BAIK has been running well. The employees have also understood their duties and obligations in implementing the SI MAS BAIK application in accordance with the SOP; 2) The efforts needed to improve the evaluation of the SI MAS BAIK application include the development of Human Resources and the improvement of facilities and infrastructure. This is done in order to improve services and utilization of the SI MAS BAIK application. Keywords: Program Evaluation, SI MAS BAIK Application, Quality of Public Service